Prosedur Pemilihan Media dan Sumber Belajar untuk Jenjang MI/SD - Meifa Taskia Efendy; Najwa Naumira Hasibuan; Rendy Ardiansyah (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
The selection of learning media and resources is an important aspect of the learning process. Learning media helps to convey material in a more engaging and effective way, while learning resources include a variety of references that support learning activities, such as human, print, visual, and audio-visual materials. The selection of media must be adjusted to the learning objectives, student characteristics, and availability of facilities. Learning resources, on the other hand, must meet the criteria of economy, practical, easy to obtain, flexible, and can motivate and support the learning process. By choosing the right learning media and resources, learning becomes more effective, engaging, and relevant for students. The method used by the researcher is qualitative research. And the data obtained were analyzed using the literature study method.